Rediseño interiorista del Mercado La Merced en la ciudad de Riobamba - Verdesoto Herrera, Alexandra Estefanía (2017)
The city of Riobamba is made up of 246,891 inhabitants, has several types of markets and each one for different business activities. One of the most important is the Market la Merced where it is planned to carry out the interior redesign to improve the functionality, aesthetics, lighting and other characteristics that make him suitable spaces for the sale of food, also apply multifunctional furniture for different types of products, and thus meet the needs of users. The dance of the tapes has been the inspiration for the application of the concept for its multiculturalism and diversity, the colors used are part of the traditional dress of indigenous Ecuadorians. Within the market an interior redesign that favors the activities with respect to architectural space will be made. The structure will remain intact but changes will apply to finished floors, walls and lying to improve their appearance and health. It aims to create areas for each trader, distributed according to their activities and needs regarding the physical space. Local, food and juices will have washing areas, preparation, storage and display.